Methods of proof and evidentiary requirements in divorce cases: an Islamic perspective - Ramlee, Zulfakar; Abdul Malek, Normi (International Islamic University Malaysia, 2008)

(untitled)
The bulk of Shariah Court cases nowadays involve matters pertaining to the dissolution of marriage. The most common ones are talaq, ta'liq and fasakh. The reason as to why the Shariah Courts are crammed with these cases is not merely due to the increasing number of divorce cases but can also be attributed to the difficulty in proving them. Today, as lifestyles become more complicated, talaq is no longer the same as talaq, previously understood. The husband no longer pronounces it openly or orally. Current technology such as SMS and email has overshadowed the sanctity of talaq. The situation becomes worse when the sender, that is the husband, denies it.